Basophil degranulation induced by cigarette smoking in man. Issue 10 (October 1982) - Walter, S; Walter, A
Abstract : There is some evidence that histamine could be a mediator of the immediate broncho-constriction that follows cigarette smoking. Since the chief reservoir of histamine in normal human blood is the basophil, we studied the acute effects of cigarette smoking on these cells. Capillary blood samples were obtained from 27 healthy young male smokers, before and 10 minutes after smoking. Basophils were collected and concentrated from these samples by a millipore membrane filter technique, stained with toluidine blue, and classified according to the staining characteristics and location of their cytoplasmic granules. This classification differentiated the "intact" from the "degranulated" basophils. A significant increase in degranulated cells and decrease in intact cells (p less than 0.001) was observed after smoking. Since histamine is present in the basophil granules, these findings suggest that cigarette smoking causes histamine release.